Thiophene-S, S-dioxidized indophenines as high performance n-type organic semiconductors for thin film transistors. Issue 51 (9th May 2016) - Deng, Yunfeng; Sun, Bin; Quinn, Jesse; He, Yinghui; Ellard, Jackson; Guo, Chang; Li, Yuning
Abstract : Three thiophene- S, S -dioxidized indophenines with deep frontier energy levels are synthesized from isatins and thiophene, which exhibit n-type semiconductor performance with high electron mobility of up to 0.11 cm 2 V −1 s −1 in thin film transistors. Abstract : The synthesis of three new isomerically pure ( E, E, E )-form thiophene- S, S -dioxidized indophenine (IDTO) compounds, (3 Z, 3′ Z )-3, 3′-(( E )-1, 1, 1′, 1′-tetraoxido-5 H, 5′ H -[2, 2′-bithiophenylidene]-5, 5′-diylidene)bis(1-dodecyl-indolin-2-one) (4a-S1 ), (3 Z, 3′ Z )-3, 3′-(( E )-1, 1, 1′, 1′-tetraoxido-5 H, 5′ H -[2, 2′-bithiophenylidene]-5, 5′-diylidene)bis(5-bromo-1-dodecyl-indolin-2-one) (4b-S1 ) and (3 Z, 3′ Z )-3, 3′-(( E )-1, 1, 1′, 1′-tetraoxido-5 H, 5′ H -[2, 2′-bithiophenyldene]-5, 5′-diylidene)bis(6-bromo-1-dodecyl-indolin-2-one) (4c-S1 ), and their use as n-channel semiconductors for organic thin film transistors (OTFTs) are reported. Compared to the non-oxidized parent indophenine compound 3, 3′-(5 H, 5′ H -[2, 2′-bithiophenylidene]-5, 5′-diylidene)bis(1-dodecylindolin-2-one) (3a ), 4a-S1 exhibited significantly lower HOMO and LUMO energy levels. Having bromine atoms at the 5, 5′- (4b-S1 ) or 6, 6′-positions (4c-S1 ), the HOMO and LUMO energy levels further decreased. In OTFT devices, these IDTO compounds exhibit unipolar n-type semiconductor behavior due to their significantly deeper LUMO and HOMO energy levels than those of3a that shows ambipolar charge transport performance. The maximum electron mobilities of4a-S1, 4b-S1 and4c-S1 are in the order of 10 −2 to 10 −1 cm 2 V −1 s −1, which are much higher than that of3a (∼10 −3 cm 2 V −1 s −1 ), originating from the lower LUMO energy levels and the high isomeric purities of the former compounds. Among the three IDTO compounds, 4c-S1 shows the highest electron mobility of up to 0.11 cm 2 V −1 s −1, which is likely due to its most extended π-electron delocalization on the LUMO wavefunction.